2019
DOI: 10.1186/s13049-019-0649-8
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital management provided by medical on-scene commanders in tunnel incidents in Oslo, Norway – an interview study

Abstract: Background High demands are placed on the emergency medical services to handle rescue operations in challenging environments such as tunnels. In Oslo, Norway a specialised management function within the emergency medical services, the medical on-scene commander, in line with the command structure within the police and fire brigade, might support or take over command and control from the ambulance incident officer arriving as the first ambulance personnel on scene. The aim was to shed light on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…One question that caused a burden to the commanders pertained to the responsibility for the safety and security of colleagues. The same issue has been described among prehospital incident commanders during tunnel incidents 24 and terrorist attacks. 18 During the interviews, reflections about the acceptable levels of risks, formal and moral obligations, legal and professional responsibilities of ambulance personnel in general were raised, as well as dilemmas in the specific context of a major incident.…”
Section: Discussionmentioning
confidence: 54%
“…One question that caused a burden to the commanders pertained to the responsibility for the safety and security of colleagues. The same issue has been described among prehospital incident commanders during tunnel incidents 24 and terrorist attacks. 18 During the interviews, reflections about the acceptable levels of risks, formal and moral obligations, legal and professional responsibilities of ambulance personnel in general were raised, as well as dilemmas in the specific context of a major incident.…”
Section: Discussionmentioning
confidence: 54%
“…In such a case the incident might escalate, resulting in negative consequences such as a time delay. Hylander et al (2019) conclude in a study concerning on-scene commanders that a mutual understanding among the emergency services could improve efficiency and decrease time arguing at the scene. Also at the strategic level, there is a need to create collaboration among the stakeholders from the involved organizations to improve the multi-agency response in emergencies in extreme environments to avoid unnecessary time loss (Stierna Doohan et al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…8 29 30 According to the senior function for prehospital medical management developed in Oslo, the EMS shows a more active attitude and uses the policy of 'safe enough' instead of 'entirely safe'. 6 The 'safe enough' policy might be a new approach for some, and more research, and perhaps even new legislation, is needed before there can be a change in attitude within the Swedish EMS.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with experiences from Oslo showing that mutual trust improves on-site collaboration. 6 Others have also shown that it is beneficial to have a pre-existing bond between the emergency services officers before managing an emergency together. 31 In this study, other collaborative organisations, such as the RTCC, were asked to be included in the collaboration forum because this was perceived to improve on-site collaboration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation